2014
DOI: 10.1016/j.chemosphere.2013.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of dimethoate chlorination during drinking water treatment

Abstract: h i g h l i g h t sThe reaction of DMT with chlorine was of first-order in each reactant. The observed rate constant of DMT degradation was strongly pH dependent. Both bromide and humic acid promoted but ammonium inhibited the degradation of DMT. Three organic byproducts were detected in DMT degradation by chlorine. The toxicity of DMT solution obviously increased after chlorination. a r t i c l e i n f o a b s t r a c t Dimethoate (DMT), a commonly used organophosphorus pesticide, is of great concern because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Some organophosphorus and carbamate insecticides are more easily hydrolyzed under alkaline conditions. Tian reported that the degradation rate of dimethoate by free chlorine was highly pH dependent, and methiocarb degradation pathways also exhibit a strong pH dependence . According to our results, soil pH could have a substantial impact on the control efficacy of dimethoate on mites, and soil pH values of 6.70 or 5.70 with a low amount of 1.50 kg ha –1 dimethoate caused mite mortalities >60% 7 days after the treatment.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Some organophosphorus and carbamate insecticides are more easily hydrolyzed under alkaline conditions. Tian reported that the degradation rate of dimethoate by free chlorine was highly pH dependent, and methiocarb degradation pathways also exhibit a strong pH dependence . According to our results, soil pH could have a substantial impact on the control efficacy of dimethoate on mites, and soil pH values of 6.70 or 5.70 with a low amount of 1.50 kg ha –1 dimethoate caused mite mortalities >60% 7 days after the treatment.…”
Section: Discussionsupporting
confidence: 64%
“…Tian reported that the degradation rate of dimethoate by free chlorine was highly pH dependent, and methiocarb degradation pathways also exhibit a strong pH dependence. 21,22 According to our results, soil pH could have a substantial impact on the control efficacy of dimethoate on mites, and soil pH values of 6.70 or 5.70 with a low amount of 1.50 kg ha -1 dimethoate caused mite mortalities >60% 7 days after the treatment. Obviously, soil pH should be given full consideration before practical drip irrigation of an insecticide in different Table 9.…”
Section: Discussionmentioning
confidence: 61%
“…To evaluate the catalytic ability of the designed LDH materials, the photocatalytic degradation of a model dye, orange II, was investigated under UV light irradiation. Indeed, catalytic degradation reactions have been proposed as highly advanced oxidation processes (AOPs), and widely used for the remediation of the wastewater in lieu of traditional methods such as chlorination or filtration . Generally, the hydroxyl and superoxide radicals that are catalytically generated by photoactive materials are responsible for the degradation of organic pollutants , .…”
Section: Resultsmentioning
confidence: 99%
“…There are no obvious differences among the HNM yields at pH 5.0e7.0, while the HNM formation amounts decreased in alkaline circumstance with the minimum value of 9.2 and 4.0 mg L À1 at pH 9.0 for RNTD and NZTD, respectively. The pK a of RNTD, NZTD and HOCl were 8.7, 6.8, and 7.5, respectively (Degim et al, 2001;Tian et al, 2014). As RNTD and NZTD are prone precursors of HNMs during chlorination, it is speculated that the both the neutral and anionic species of RNTD and NZTD contributed to the HNMs formation.…”
Section: Hnmsfp Of Rntd and Nztdmentioning
confidence: 99%